Peran Pemerintah dan Swata Dalam Perekonomian - Dwi Candra Putra (CV. ULIL ALBAB CORP, 2022)
Government is a system for exercising authority and power in regulating the social, economic and political life of a country or its parts. Another definition of government is a group of people who jointly assume limited responsibility for exercising power. Government can also be interpreted as the ruler of a country or the highest body that governs a country. Basically the government sector can be categorized into the public sector. The public sector is an organization of state economic entities to carry out their duties as controllers of society towards prosperity. This control is in the form of providing useful services to the public. Institutionally, the public domain includes government non-profit organizations and non-governmental non-profit organizations. Government agencies such as the central government, regional governments, and other government work units, are forms of government organizations. While the forms of non-profit non-governmental organizations are volunteer organizations, private hospitals, private high schools and universities, foundations, NGOs, BUMN/BUMD, religious organizations, political organizations, and so on. Qualitative descriptive. that the role of the government and the private sector is seen to be very important in supporting the economy. In addition, the center of economic development is the development of supporting and adequate infrastructure. With limited funds as well as APBN or APBD owned by the government, the role of the private sector in the involvement of infrastructure development is very much needed. The private sector can contribute to the development and financing of infrastructure that has been planned by the government. However, this does not mean that the private sector takes a full role in infrastructure financing, but that the role of the government as a regulator is indispensable in controlling and overseeing infrastructure so that it can be used with the community as well as possible.